2022
DOI: 10.30819/iss.44-2.03
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of current support systems leading to international sporting success for South Africans

Abstract: The purpose of the study was to examine the availability of elite sport support systems of South African National Sports Federations (NSFs) and their accessibility to athletes from historically disadvantaged areas (HDA). Twenty-one NSFs from Olympic sports participated in the study whereby they responded to a questionnaire on sports policy factors leading to sporting success (SPLISS). Descriptive statistical analyses were conducted using the Statistical Package for Social Sciences (SPSS version 27.0, IBM). Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, without scholarships or financial support to attend such elite schools, athletes from HDA have a limited competitive advantage compared to their wealthy peers in well-resourced schools. This finding is consistent with that of Mthombeni et al 17 who found that most former Olympians from HDA reported a lack of financial support, especially at the development level, being among the major hindrances of sporting success in South Africa. The lack of financial support may stem from the poor budget allocation to sports by government annually.…”
Section: Lack Of Financial Supportsupporting
confidence: 92%
See 3 more Smart Citations
“…However, without scholarships or financial support to attend such elite schools, athletes from HDA have a limited competitive advantage compared to their wealthy peers in well-resourced schools. This finding is consistent with that of Mthombeni et al 17 who found that most former Olympians from HDA reported a lack of financial support, especially at the development level, being among the major hindrances of sporting success in South Africa. The lack of financial support may stem from the poor budget allocation to sports by government annually.…”
Section: Lack Of Financial Supportsupporting
confidence: 92%
“…This finding is consistent with that of Mthombeni et al 45 who found that 52% of South African NSFs in their study reported they were unable to invest in scientific support programmes for their elite athletes because of insufficient funding from the national government. Kubayi et al 9 found a dire need for scientific research and support by South African coaches in areas of technique efficiency, sports injury prevention, athlete peak performance and the mental preparation of athletes for competitions.…”
Section: Hindrancessupporting
confidence: 92%
See 2 more Smart Citations
“…In most cases there is no support in such instances unless you make the team go compete at Olympics, then in weeks before the games, you will have access to some sort of scientific testing or high-performance testing sessions.' (Athlete 4) Mthombeni, Coopoo, and Noorbhai [25] reported similar findings when evaluating the availability of support systems by South African national sport federations, whereby majority reported a lack of scientific support programmes within their administration. Sports science research and scientific support leads to evidence-based training regimes that allow athletes to perform optimally.…”
Section: Poor Scientific Supportmentioning
confidence: 68%